Effects of electron beam irradiation on the thermal properties of scrap polytetrafluoroethylene - Sivanesan Appadu; Chantara Thevy Ratnam; Sahrim Ahmad; Ruey, Shan Chen; Teo, Ming Ting; Gupta, Thummalapalli C.S.M. (Universiti Kebangsaan Malaysia, 2022)
This study is focused on analyzing the effects of electron beam (EB) irradiation at high doses and normal atmospheric conditions on the thermal stability of scrap polytetrafluoroethylene (PTFE) solid to facilitate the recycling process of the material by grinding it into micro-powder additives for various applications. In this work, PTFE scrap with thickness not exceeding 1 mm was irradiated in doses between 0 - 1500 kGy using an electron beam accelerator machine (EBM) with a voltage energy of 3 MeV and current of 10 mA and grinded into powder by using a laboratory mill. The changes in morphology of the grinded powder, crystallinity and thermal properties of PTFE with increasing irradiation dose was studied by using scanning electron microscopy (SEM), X-ray diffraction (XRD) analysis, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The photomicrographs obtained from SEM showed that the particle size of the grinded micro-powder decreases with increasing irradiation dose with best results observed at 1500 kGy dose. DSC analysis showed that the crystallization temperature (Tc) and melting temperature (Tm) decreases with increasing irradiation doses as a result of lower molecular weight. XRD analysis of the irradiated PTFE indicated that the intensity of the peak had increased with increasing doses of irradiation due to the increase in crystallinity of the material. The distinctly shorter derivative thermogravimetric (DTG) peak height at 1500 kGy shows higher rate of mass loss at that dose due to the rapid loss of mechanical properties caused by degradation.